2021
DOI: 10.21037/atm-20-4942
|View full text |Cite
|
Sign up to set email alerts
|

Real-world results of the implementation of preoperative anaemia clinic with intravenous iron therapy for treating iron-deficiency anaemia: a propensity-matched case-control study

Abstract: Background: Preoperative anaemia is associated with blood transfusion and longer hospital length of stay.Preoperative iron deficiency anaemia (IDA) can be treated with oral or intravenous (IV) iron. IV iron can raise haemoglobin faster compared with oral iron. However, its ability to reduce blood transfusion and length of stay in clinical trials is inconclusive. This study aims to compare blood transfusion and hospital length of stay between anemic patients who received preoperative IV iron versus standard car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 53 publications
(66 reference statements)
0
32
0
Order By: Relevance
“…Respondents were not asked to identify surgeries that were impacted explicitly. Yet, this finding could provide insight into the evaluation and treatment of preoperative anemia (another patient blood management program component 23 ), the benefits of which might include decreased blood transfusions, not to mention improved outcomes and shorter length of hospital stay 24–28 . Notably, a recent randomized controlled trial showed that patients receiving iron supplementation were not transfused less blood compared to patients who did not receive iron up to 42 days before major abdominal surgery 29 …”
Section: Discussionmentioning
confidence: 99%
“…Respondents were not asked to identify surgeries that were impacted explicitly. Yet, this finding could provide insight into the evaluation and treatment of preoperative anemia (another patient blood management program component 23 ), the benefits of which might include decreased blood transfusions, not to mention improved outcomes and shorter length of hospital stay 24–28 . Notably, a recent randomized controlled trial showed that patients receiving iron supplementation were not transfused less blood compared to patients who did not receive iron up to 42 days before major abdominal surgery 29 …”
Section: Discussionmentioning
confidence: 99%
“…25 One nonrandomized study was published in 2022, 26 while 5 non-randomized studies were published in 2021. [27][28][29][30][31] Five of the non-randomized studies were retrospective cohort studies that used historical patient data in their analysis. [26][27][28][29][30] One non-randomized study was a multicenter prospective cohort study that used prospectively collected patient data.…”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29][30][31] Five of the non-randomized studies were retrospective cohort studies that used historical patient data in their analysis. [26][27][28][29][30] One non-randomized study was a multicenter prospective cohort study that used prospectively collected patient data. 31 When reported, patient follow-up time varied across studies depending on the outcome being reported, but ranged from 21 days to 3 months.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations